ANALISIS RISIKO DALAM PROSES PENGADAAN JASA DI RU III MENGGUNAKAN PENDEKATAN HOUSE OF RISK (HOR) - Rahmad Inca Liperda; Dinda Tasya Salsabila (INFOTECH journal, 2023)
This study analyzes risks in the procurement process of services in RU III using the House of Risk (HOR) approach to enhance risk management effectiveness. Risk identification is conducted through observation, interviews, and relevant literature review. The analysis of HOR phase 1 identifies three best risk mitigation strategies: coordination with vendors/FPP before open registration (PA1), clarification of technical and administrative documents (PA2), and maximum negotiation and tender reprocessing if below Pertamina's HPS (PA3). HOR phase 2 involves calculating the Total Effectiveness Value (TEk) and the Efficiency Difficulty Ratio (ETDk) to evaluate the effectiveness and implementation difficulty of the mitigation strategies. This research provides recommendations for implementing the identified mitigation strategies and periodic monitoring to enhance risk control. The findings of this study contribute to the development of service procurement risk management in RU III and serve as a reference for decision-makers in risk mitigation during the service procurement phase.